Do informative leaflets affect pre-procedural anxiety and immediate pain after transforaminal epidural steroid injections? A prospective randomized controlled study - GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (KARE PUBL, 2020)
Objectives: The aim of this study was to evaluate the effect of an informative leaflet provided to patients before a lumbar transforaminal epidural steroid injection (TFESI) on the level of immediate pain and pre-procedural anxiety. Methods: A total of 166 patients were randomized into 2 groups: a group that received an explanatory leaflet (LG) and a control group. Both groups were given verbal information, while the LG was also given an illustrated leaflet describing the injection process. All of the patients were evaluated with the Hospital Anxiety and Depression Scale before the TFESI. The numerical rating scale and the Oswestry Disability Index (ODI) were used to assess disability and pain before and after the TFESI. Major complications that occurred before and during the procedure were recorded and analyzed. Results: The patient characteristics were similar in both groups (age, body mass index, depression level, pre-procedural pain, and ODI). The anxiety level was also similar in both groups (p>0.05). When both groups were evaluated at the first hour after the procedure, the numerical rating scale level of pain intensity was also similar (p>0.05). No major complication was observed in either group. Conclusion: The detailed leaflet did not affect the patients' pre-procedural anxiety or acute post-procedural pain level. However, the importance of informed consent and comprehensive information should not be overlooked.
Keywords: Anxiety; disc herniation; informative leaflet, low-back pain; lumbar radiculopathy; transforaminal epidural steroid injection